Metamazarredia is Rosacris is Mazarredia (Orthoptera: Tetrigidae)—a long-awaited sequel to a taxonomic dilemma - Kasalo, Niko (Zootaxa, 2022)
The monotypic genus Rosacris, described by Bolívar (1931) remained largely unnoticed until a couple of new specimens were noticed by Skejo (2016), which prompted his examination of the genus and the conclusion that R. antennata syn. nov. probably represents a nymph of Metamazarredia fuscipes (Stål, 1877). By not conducting taxonomic acts, Skejo (2016) left behind an important dilemma: are the two species actually synonymous with each other? This paper reexamines the available material and concludes that the aforementioned observation was correct. Mazarredia (Rosacris) fuscipes comb. nov. represents the current combination used for the two synonymous species as the generic name of Rosacris stat. nov. has priority over Metamazarredia syn. nov., but the specific epithet “antennata” does not. Rosacris stat. nov. is considered a subgenus of Mazarredia Bolívar, 1887 because it shares many differences with the nominal subgenus, differing only by having a vertex twice as wide as an eye, and possibly by having some antennal segments widened and the median carina of the pronotum being slightly elevated in its anterior part. Mazarredia (Rosacris) sobria (Walker, 1871) comb. nov. is transferred to the subgenus Rosacris due to its wide vertex and the anteriorly elevated median carina. The genus Mazarredia includes many species and needs revision.